Spermiotaxonomy of the tribe Rhodniini (Hemiptera, Triatominae) - Ravazi, A. [UNESP]; Oliveira, J. [UNESP]; Rosa, J. A. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP]; Alevi, K. C. C. [UNESP] (Funpec-editora, 2016)
The tribe Rhodniini is a monophyletic group composed of 22 species, with 19 in the Rhodnius genus and three in the Psammolestes genus. These insects are morphologically very similar (cryptic species), and new tools are important for investigating the taxonomy of these vectors. Spermiotaxonomy is an important tool in differentiating between related species, and this study analyzed the spermatids of Rhodniini species to elucidate their spermiotaxonomy. All of the Rhodniini species contained two heteropyknotic filaments in the extremities of their cells. Although spermiotaxonomy has been an important tool in differentiating between species of the Triatoma genus, all of the species in the Rhodnius genus exhibited the same characteristics in their male gametes. However, spermatid analysis made it possible to confirm the monophyly of the Rhodniini tribe, because Psammolestes tertius had the same pattern as that described for Rhodnius. The results of this study demonstrate that spermiotaxonomy, in addition to being an important tool for differentiating between related species of Triatoma, can be used as an optimization tool in phylogenetic analyses.
Keywords: Rhodnius; Psammolestes; Spermiogenesis; Cytotaxonomy